ANALISA PENGEMBALIAN MODAL PADA PETERNAKAN AYAM PETELUR RAJIMAN DI TANJUNG BINTANG - Putri Suwarni; Sunarto Sunarto (Fakultas Teknik Universitas Tulang Bawang Lampung, 2018)
The price of chicken eggs continue to fluctuate up and down where feed prices tend not to rise. This is an interesting phenomenon to be examined. The purpose of this study is to analyze Pak Rajiman's chicken farming business that has been running for 1 year, whether it is feasible or not to run. The data were taken from interviews and field observations in the form of livestock business financial data, starting from capital, production and receipt costs obtained for 1 year. The data were processed and analyzed by regression equations, Benefit/Cost (B/C) Ratio calculations and Break Even Points analysis. And there is a significant influence of feed prices with the quality of feed and egg production produced. And from the cost benefit analysis, the B/C value> 1 is obtained, then chicken farm is said to be feasible and Break Even Point (BEP) value at 4,193 kg of egg production, equivalent to 5.1 months.